Collections held by the British Library (as filmed by the AJCP) [M2669-2677] - British Library; Australian Joint Copying Project; National Library of Australia; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1987)
Includes various manuscripts from Sloane, Egerton, Hargrave and Temple-Grenville (known as the Stowe manuscript). Additional manuscripts are also present. The subject matter of the above items relate mainly to Australian and Pacific topics. Material in the collection includes (amongst others): The journals of William Dampier and W.A. Cowley; papers on New South Wales; notes on zoology; papers of James Cook; items relating to "For the term of his natural life"; various correspondence and so on.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project miscellaneous series M2669-2677.
Also available online
Microfilm.
Microfilm copy of originals held by the British Library, Great Russell Street, London. WC1B 3DG.
Keywords: Sloane, Hans, -- Sir, -- 1660-1753 -- Archives; Egerton, Francis, -- Rev., -- 1756-1829 -- Archives; Temple-Grenville, Richard -- 1776-1839 -- Achives; Dampier, William, -- 1652-1715 -- Diaries; Hargrave, Francis, -- 1741?-1821 -- Archives; Cowley, William Ambrosia -- Diaries; Cook, James, -- 1728-1779 -- Archives; Clarke, Marcus, -- 1846-1881